Walking along the oldest human fossil pathway (Roccamonfina volcano, Central Italy)?. (June 2017) - Panarello, Adolfo; Santello, Lisa; Farinaro, Gennaro; Bennett, Matthew R.; Mietto, Paolo
Abstract: Here we report the remarkable superposition of a pre-historic trackway (349–350 ± 3 ka) with one used in more recent historical times, potentially forming one of the oldest path or trackways currently known. A Plinian eruption of the Roccamonfina Volcano resulted in a succession of pyroclastic flows. A combination of syn-sedimentary erosion and depositional morphology resulted in a bench, contouring the depositional slope. Prior to rapid lithification of the flow, early human ancestors used the bench as a route-way. At least two individuals diverted from this route-way to make the famous Trackways A and B of the Devil's Trails which have been described previously. The bench and associated animal tracks were covered by subsequent pyroclastic ash falls before being exhumed in historical times by a combination of natural erosion and quarrying. The bench was re-used as a route-way at this time and some of the tracks modified by human action to improve surface conditions and perhaps drainage. The P1-Trackway is the result and its detailed morphology is described here. Not only does it provide remarkable evidence of the convergence of route-ways through time along key geomorphological features in the landscape but the palimpsest of tracks provides a useful case study for archaeologists and ichnologists interpreting complex and superimposed surface traces. Highlights: New findings within Roccamonfina paleontological site Report on what is probably the oldest human fossil path or trackway ever found Multiple occupation/use of topographic benches and terraces Archaeology and 3D modelling to demonstrate actuality of ichnological evidence